Enhancing immunity in viral infections, with special emphasis on COVID-19: A review. Issue 4 (July 2020) - Jayawardena, Ranil; Sooriyaarachchi, Piumika; Chourdakis, Michail; Jeewandara, Chandima; Ranasinghe, Priyanga
Abstract: Background and aims: Balanced nutrition which can help in maintaining immunity is essential for prevention and management of viral infections. While data regarding nutrition in coronavirus infection (COVID-19) are not available, in this review, we aimed to evaluate evidence from previous clinical trials that studied nutrition-based interventions for viral diseases (with special emphasis on respiratory infections), and summarise our observations. Methods: A systematic search strategy was employed using keywords to search the literature in 3 key medical databases: PubMed®, Web of Science® and SciVerse Scopus®. Studies were considered eligible if they were controlled trials in humans, measuring immunological parameters, on viral and respiratory infections. Clinical trials on vitamins, minerals, nutraceuticals and probiotics were included. Results: A total of 640 records were identified initially and 22 studies were included from other sources. After excluding duplicates and articles that did not meet the inclusion criteria, 43 studies were obtained (vitamins: 13; minerals: 8; nutraceuticals: 18 and probiotics: 4). Among vitamins, A and D showed a potential benefit, especially in deficient populations. Among trace elements, selenium and zinc have also shown favourable immune-modulatory effects in viral respiratory infections. Several nutraceuticals and probiotics may also have some role in enhancing immune functions. Micronutrients may be beneficial in nutritionally depleted elderly population. Conclusions: We summaries possible benefits of some vitamins, trace elements, nutraceuticals and probiotics in viral infections. Nutrition principles based on these data could be useful in possible prevention and management of COVID-19 Highlights: Supplementation of Vitamin A, D and Zn and selenium may be beneficial for both prevention and treatment of viral infections. Several nutraceuticals and probiotics can enhance immunity against viral infection. Patients with malnutrition, diabetes and obesity require personalized nutrition advices during this pandemic of COVID-19.